2000
DOI: 10.1037/0033-295x.107.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Naive empiricism and dogmatism in confidence research: A critical examination of the hard–easy effect.

Abstract: Two robust phenomena in research on confidence in one's general knowledge are the overconfidence phenomenon and the hard-easy effect. In this article, the authors propose that the hard-easy effect has been interpreted with insufficient attention to the scale-end effects, the linear dependency, and the regression effects in data and that the continued adherence to the idea of a "cognitive overconfidence bias" is mediated by selective attention to particular data sets. A quantitative review of studies with 2-alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
295
7
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(320 citation statements)
references
References 76 publications
13
295
7
5
Order By: Relevance
“…Because they are imperfect, they will naturally tend to be overconfident when they are very confident, but also underconfident when they are very unconfident. Recent research with binary questions has in general supported this view (e.g., Juslin, Winman, & Olsson, 2000;Klayman et al, 1999). Overconfidence may have been the predominant finding in earlier studies because of a tendency for experimenters to construct tests that favored the harder questions in any given domain.…”
Section: Overconfidence In Interval Estimatesmentioning
confidence: 90%
“…Because they are imperfect, they will naturally tend to be overconfident when they are very confident, but also underconfident when they are very unconfident. Recent research with binary questions has in general supported this view (e.g., Juslin, Winman, & Olsson, 2000;Klayman et al, 1999). Overconfidence may have been the predominant finding in earlier studies because of a tendency for experimenters to construct tests that favored the harder questions in any given domain.…”
Section: Overconfidence In Interval Estimatesmentioning
confidence: 90%
“…Therefore, the impact of representative design can now be studied across a wide range of studies. Recently, P. Juslin, Winman, and Olsson (2000) conducted a review of 130 overconfidence data sets to quantify the effects of representative and unrepresentative item sampling. Figure 4 depicts the over-and underconfidence scores (regressed onto mean confidence) observed in those studies.…”
Section: Does "Overconfidence" Disappear In Representative Designs?mentioning
confidence: 99%
“…Yet these experts lacked incentives rewarding accuracy, training in the use and interpretation of probability scales, and practice, and perhaps most importantly, they lacked timely and unambiguous feedback (Benson and Onkal 1992, Hoelzl and Rustichini 2005, Larrick 2004). Research has found that each of these can help reduce overconfidence, but effects have generally been studied over short time horizons, usually constrained by the duration of laboratory experimental sessions (Soll et al 2016 questions about the degree to which these debiasing effects generalize over longer time horizons and in more consequential domains (Dawes and Mulford 1996, Gigerenzer 1991, Juslin et al 2000.…”
Section: Introductionmentioning
confidence: 99%